Stomatal and photochemical limitations of photosynthesis in coffee (Coffea spp.) plants subjected to elevated temperatures - Rodrigues, Weverton P; Silva, Jefferson R; Ferreira, Luciene S; Filho, José A. Machado; Figueiredo, Fabio A. M. M. A; Ferraz, Tiago M; Bernado, Wallace P; Bezerra, Luan B. S; de Abreu, Deivisson P; Cespom, Letícia; Ramalho, José C; Campostrini, Eliemar (Crop and pasture science, 2018)
Temperature increase assumes a prominent role in the context of expected climate change because of its significant impact on plant metabolism. High temperature can affect the carbon-assimilation pathway at both stomatal and non-stomatal levels, mainly through stomatal closure and photochemical and biochemical limitations. In general, however, plants have some ability to trigger acclimation mechanisms to cope with stressful conditions, especially if the limitations are imposed in a gradual manner during seasonal change. This study aims at evaluating changes at stomatal and photochemical levels in Coffea arabica and C. canephora under exposure to mild temperature (spring) and high temperature (summer). Potted plants were maintained in a greenhouse, watered to field capacity and subject to natural variations of light, temperature and relative humidity. In C. arabica, exposure to summer conditions decreased photosynthetic rates (A), stomatal conductance (gs) and stomatal density and increased intrinsic water-use efficiency (iWUE) compared with spring values, whereas C. canephora plants maintained similar values in both seasons. However, C. canephora presented lower A and gs during spring than C. arabica. Because photosynthetic capacity (Amax), photosynthetic performance index and membrane permeability were similar between genotypes and seasons, and maximum quantum yield (Fv/Fm) and photosynthetic pigments were not affected in C. arabica in summer, we conclude that under high temperature conditions, stomatal closure imposes the major limitation on C. arabica photosynthesis in summer. Finally, both coffee genotypes were able to avoid damage to photochemistry pathway under supra-optimal temperatures.